Biodegradation behavior of palm oil fiber reinforced starch biocomposite - Tuan Rosmina, Tuan Ismail (2010)
The use of biodegradable materials from renewable resources had gained more attention in recent years. This research focus on the production of biocomposite from starch, glycerol and palm oil fiber whereby the fiber composition were 0%, 5%, 10%, 15% and 20%. The biocomposite produced was characterized in physical and chemical properties using Universal Testing Machine, Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR), Differential Scanning Calorimetry (DSC), microbial degradation and soil burial degradation. This study revealed that the tensile strength increased by the addition of fiber until 10% but when the fiber compositions more than 10%, the tensile strength starts to decrease because of the poor adhesion between fiber and starch. On the thermal properties, the addition of fiber in the biocomposite improves the thermal stability as the melting point of the biocomposites increases when the fiber composition increased. For the biodegradability test, as the fiber composition increased, the longer time needed for the biocomposite to be degraded. Thus, the best performance of the biocomposites reinforced with fiber was at 10% fiber composition due to its higher mechanical testing and higher melting temperature. As a conclusion, the addition of fiber as a reinforcement in starch biocomposite can improve its mechanical strength, thermal properties and biodegradability whereby it had a various applications for biocomposites such as toys for children, furniture, flooring, and hardware for electronic products.